The role of phytoliths in archaeological research; An interpretative approach: The role of phytoliths in archaeological research; An interpretative approach (Revista revoluciones, 2023)
The analysis of phytoliths is a tool that in recent years has exponentially increased its importance in archaeological research, trying to understand the interaction of humans with the plant world in the past, since, due to their mineralogical characteristics, they have a high durability and presence in substrates and objects, which makes them excellent paleoindicators. However, in spite of their potential and importance, in many regions of Latin America, the analysis of phytoliths is in a state of confusion, due to the existing doubts about their potential and scope of resolution. This is the reason for the present essay, which starts by answering questions such as: What are phytoliths?  It aims to dispel and clarify some of the questions surrounding the study of these structures in archaeological research
Keywords: Phytoliths; questions; archaeological research; research potential